2019
DOI: 10.1075/target.18091.chm
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic processing in sight translation by professional and trainee interpreters

Abstract: The study examines how professional and trainee interpreters process syntax in sight translation. We asked 24 professionals and 15 trainees to sight translate sentences with subject-relative clauses and more difficult object-relative clauses while measuring translation accuracy, eye movements and translation durations. We found that trainees took longer to achieve similar translation accuracy as professionals and viewed the source text less than professionals to avoid interference, especially when reading more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Lexical and morphosyntactic properties of both SL and TL are activated upon reading the SL, as comprehension and reformulation take place simultaneously. Previous research finds overwhelming support for the horizontal perspective (Macizo & Bajo, 2006;Ruiz et al, 2008;Seeber & Kerzel, 2011;Chmiel & Lijewska, 2019), and a substantial body of evidence points to coactivation of both languages during bilingual comprehension and production (Kroll et al, 2006;Marian, Spivey & Hirsch, 2003). In accordance with such evidence, it can be predicted that the mechanisms of the two working languages are simultaneously active and interact in a parallel manner when processing the source text and its MT output.…”
Section: Visual Presentationmentioning
confidence: 91%
See 2 more Smart Citations
“…Lexical and morphosyntactic properties of both SL and TL are activated upon reading the SL, as comprehension and reformulation take place simultaneously. Previous research finds overwhelming support for the horizontal perspective (Macizo & Bajo, 2006;Ruiz et al, 2008;Seeber & Kerzel, 2011;Chmiel & Lijewska, 2019), and a substantial body of evidence points to coactivation of both languages during bilingual comprehension and production (Kroll et al, 2006;Marian, Spivey & Hirsch, 2003). In accordance with such evidence, it can be predicted that the mechanisms of the two working languages are simultaneously active and interact in a parallel manner when processing the source text and its MT output.…”
Section: Visual Presentationmentioning
confidence: 91%
“…Previous studies in translation processing provide ample evidence that translation involves a process that establishes linguistic matches between the two languages in a parallel manner and that greater processing resources are needed when translation involves greater transformations (Chmiel & Lijewska, 2019;Ruiz et al, 2008;Seeber & Kerzel, 2011;Viezzi, 1989). In experimental studies that explore the processes of sentence-level translation, there are two opposing views regarding how the three cognitive processes in translation-SL comprehension, reformulation, and TL production-operate.…”
Section: Visual Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar cross-language syntactic interference has been found in translation, where translators tend to replicate syntactic structures from the original text into the translated text (e.g., [ 27 ]). Given that interpreters often prepare target language syntax while comprehending the source language (e.g., [ 23 , 24 , 28 , 29 ]), such cross-language syntactic influence might be commonplace. While this might facilitate language production in the target language when the two languages have similar structures, it could lead to syntactic speech errors when the syntactic sequence copied from the source language is illicit in the target language.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to increased cognitive effort involved in L1-to-L2 interpreting or to the need to keep the turn of the interaction. In another study, a classic professional-trainee comparison was made by Chmiel and Lijewska (2019), who found that trainees viewed source text (ST) less in STR than professionals. This could be because trainee interpreters intentionally looked away to actively avoid interference from source text.…”
Section: Viewing Patternsmentioning
confidence: 99%